2012
DOI: 10.1097/01.epx.0000417978.44502.61
|View full text |Cite
|
Sign up to set email alerts
|

Research practices and publication obstacles among interns at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, 2011–2012

Abstract: Interns in King Abdulaziz University Faculty of Medicine have a positive attitude towards research; however, few students submit papers for publication. Lack of time and training in research methods were the main obstacles cited by the interns for conducting and publishing research. Interns welcome training in research, scientific writing and publication practice. These requirements will be issued to the main curriculum committee at the faculty of medicine and recommendations on possible actions will be discus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
0
17
0
1
Order By: Relevance
“…Nevertheless, despite these limitations, it is important to note that participant responses to the anonymous survey used in the current study may have been more honest than those from other research utilising different methods of data collection. 25 …”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite these limitations, it is important to note that participant responses to the anonymous survey used in the current study may have been more honest than those from other research utilising different methods of data collection. 25 …”
Section: Discussionmentioning
confidence: 99%
“…The study questionnaire also included questions about the obstacles and barriers preventing students from conducting or participating in medical research. Barrier items included in the questionnaire (n=22 items) were formulated according to the data available in the previous qualitative studies, 2 , 5 , 9 , 10 , 14 , 15 and then categorized to include personal (n=6 items) and institutional aspects (n=16 items). Each studied barrier item was scored as follows: 1= totally disagree; 2= disagree; 3= neutral; 4= agree; 5= totally agree.…”
Section: Methodsmentioning
confidence: 99%
“…15,16 Integrating the research further into the curriculum was among the recommendations concluded from previous studies conducted at the FOM, KAU. 17,18 In response to that, the curriculum committee at the FOM encouraged integration of research skills into the course and modules. One interesting finding in the present work is the students' satisfaction regarding the newly introduced module objectives related to the scientific research skills.…”
Section: Discussionmentioning
confidence: 99%